2017
DOI: 10.1038/nrd.2017.87
|View full text |Cite|
|
Sign up to set email alerts
|

Breaking barriers to novel analgesic drug development

Abstract: Acute and chronic pain complaints, while very common, are generally poorly served by existing therapies. The unmet clinical need reflects the failure in developing novel classes of analgesics with superior efficacy, diminished adverse effects and a lower abuse liability than those currently available. Reasons for this include the heterogeneity of clinical pain conditions, the complexity and diversity of underlying pathophysiological mechanisms coupled with the unreliability of some preclinical pain models. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
257
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(261 citation statements)
references
References 288 publications
3
257
0
1
Order By: Relevance
“…[29] The approach we demonstrate here adds to the arsenal of methods for tuning the properties of disulfide-rich sequences through chemical alteration. [11] Importantly, sequence-guided backbone modification of the type described is fully complementary to existing approaches such as disulfide replacement and cyclization.…”
Section: Discussionmentioning
confidence: 99%
“…[29] The approach we demonstrate here adds to the arsenal of methods for tuning the properties of disulfide-rich sequences through chemical alteration. [11] Importantly, sequence-guided backbone modification of the type described is fully complementary to existing approaches such as disulfide replacement and cyclization.…”
Section: Discussionmentioning
confidence: 99%
“…Selective small‐molecule inhibitors of Nav1.7 and Nav1.8 channels have been found. While the only reported clinical test of a Nav1.8‐selective inhibitor resulted in a terminated trial on dental pain, clinical trials of several Nav1.7‐selective compounds are underway …”
Section: What We Need To Knowmentioning
confidence: 99%
“…It has been shown that i.t. injection of tizanidine can produce dose-dependent analgesic effects in neuropathy rats (Ou-Yang et al, 2008;Yekkirala, Roberson, Bean, & Woolf, 2017). Semenchuk and Sherman (2000) in an open-label study assessed the effectiveness and tolerability of tizanidine in neuropathy patients.…”
Section: Electrophysiological Evidence For Spinal Adrenergic Pain Imentioning
confidence: 99%